Bod kyi dus rabs rim byuṅ gi rtsom yig gces btus (Kruṅ go'i bod rig pa dpe skrun khaṅ, 2008)
Twenty-three selected works of classical Tibetan literature with explanatory footnotes, and a brief syllabus of topics for discussion (pages 333-342) and related sources
Keywords: Tibetan literature / History and criticism; Tibetan literature / History and criticism / Textbooks; Tibetan literature; Criticism; interpretation; etc; Textbooks; Literatur